Desain Media Gachapon dalam Pembelajaran Menulis Teks Puisi bagi Siswa Kelas VIII SMP - Rahmawati Mulyaningtyas; Dimas Fajar Abidin (Hiski Malang, 2025)
Learning to write poetry plays an important role in developing students' language skills, imaginative power, and emotional sensitivity. Despite its importance, poetry writing lessons often face obstacles, such as students having difficulty starting their writing, choosing diction, or finding suitable ideas. Consequently, a learning medium is needed that can stimulate creativity while helping students find ideas for writing. Gachapon media offers uniqueness because it combines elements of games, interactivity, and creativity in poetry writing lessons. Inspired by Japanese capsule toy machines, this medium utilizes random vocabulary to stimulate students' imaginations, making learning more enjoyable through play. The purpose of this research is to design and describe Gachapon media as a tool in teaching poetry writing materials in Grade VIII. This research is categorized as development research that produces a Gachapon learning media product. The development model used adapts the 4D model consisting of the define, design, and develop stages. Meanwhile, this media has not yet reached the disseminate stage due to limited time and costs. Media validation was carried out by one media expert lecturer. The results of the study show that Gachapon can be utilized as a medium in learning to write poetry in Grade VIII. However, the validation results indicate that there are several things that need to be improved, namely the paper containing vocabulary needs to be typed and there needs to be instructions for using the media.